Factors Influencing Consumer Preferences for Espresso and Omni Roasted Coffee: A Comprehensive Analysis - Maspul, Kurniawan Arif; Sidiq, Ari Rahmana (Journal of Economics and Economic Education, 2024)
This qualitative study conducted in Buraydah, Saudi Arabia, explores coffee customers' shifting preferences, with a focus on the growing popularity of espresso and multi-roasted coffee. Through interviews with consumers, baristas, and coffee roasters, the study investigates the motivations behind these choices, which include health concerns, flavor exploration, and a dislike for highly acidic coffees. The findings highlight the appeal of concentrated flavor, higher caffeine concentration, and the ability to appreciate the varied qualities of coffee beans from different places. Omni roasted coffee, with its medium-dark roast, has a balanced flavor profile that works well with a number of brewing methods. The concept of coffee terroir, which highlights the distinct flavors associated with individual origins, influences customer preferences. These findings have ramifications for coffee growers and baristas, who can meet shifting customer needs by acquiring high-quality beans and perfecting brewing procedures. This study leads to a better knowledge of changing coffee preferences and gives practical insights for industry stakeholders.